LE PSAUME 149 ET LA "VENGEANCE" DES PAUVRES DE YHWH - Tournay, Raymond Jacques 1912-1999 (1985)
Le waw initial du v. 6b est un waw adaequationis et non un waw copulatif Avec le Targum, il faut comprendre : « Les éloges de Dieu à pleine voix, comme à la main une épée à deux tranchants. » "The Psalm 149 and the "Veangeance of the Poors of YHWH." In v. 6b, the waw is a waw adaequationis, and non a waw copulative. With the Targum, we must translate: "Let the praise of God be on their lips, as a two-edged sword in their hand."